1991
DOI: 10.1007/bf00310921
|View full text |Cite
|
Sign up to set email alerts
|

Nigral degeneration in acquired immune deficiency syndrome (AIDS)

Abstract: Using stereological techniques we have estimated the volume density of melanin and counted the number of pigmented and non-pigmented neuronal cell bodies in the pars compacta of the substantia nigra of 12 autopsied patients with acquired immune deficiency syndrome (AIDS) who did not have inflammation or necrosis of the midbrain or clinical parkinsonism. The total number of neuronal cell bodies was 25% lower in AIDS (P less than 0.01) than in 12 age-matched controls, although the volume density of neuronal mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 12 publications
3
82
0
Order By: Relevance
“…Histopathological studies, demonstrating the presence of high concentrations of viral proteins in the striatum of HIV-1 seropositive patients coupled to abnormalities of the pars compacta of the SN even in the absence of clinical evidence of parkinsonism (46,47), corroborate the physiopathological implications of our findings obtained in both a cell and an animal model. In this respect, it has been recently shown that Tat can easily across the blood-brain barrier (48).…”
Section: Induction Of a Subclinical Parkinson's-like Disease Insupporting
confidence: 88%
“…Histopathological studies, demonstrating the presence of high concentrations of viral proteins in the striatum of HIV-1 seropositive patients coupled to abnormalities of the pars compacta of the SN even in the absence of clinical evidence of parkinsonism (46,47), corroborate the physiopathological implications of our findings obtained in both a cell and an animal model. In this respect, it has been recently shown that Tat can easily across the blood-brain barrier (48).…”
Section: Induction Of a Subclinical Parkinson's-like Disease Insupporting
confidence: 88%
“…Studies investigating substances of abuse and HIV infection suggest that drugs accelerate neuronal loss in HIV infection, and that dopamine, in addition to its typical neurotransmission role, can alter BBB integrity and promote leukocyte activation (see Substance abuse, HIV, and the BBB for a more comprehensive discussion of dopamine) (Reyes et al 1991;Bennett et al 1995;Herz 1995;Czub et al 2004;Wang et al 2004). …”
Section: Neurotransmitters Originating From the Cns Or Blood Acting Omentioning
confidence: 99%
“…During active infection, these structures contain among the brain's highest viral burden as well as HIV-1-infected macrophages and multinucleated giant cells (Kure et al 1990), which cause loss of dopaminergic neurons in the substantia nigra (Reyes et al 1991) and striatal atrophy (Berger and Nath 1997). Signs of parkinsonism have also been observed in the Ôacquired immune deficiency sydrome (AIDS)-dementia complexÕ (Mirsattari et al 1998).…”
mentioning
confidence: 99%